2019
DOI: 10.1186/s13287-019-1396-5
|View full text |Cite
|
Sign up to set email alerts
|

An overview on small molecule-induced differentiation of mesenchymal stem cells into beta cells for diabetic therapy

Abstract: The field of regenerative medicine provides enormous opportunities for generating beta cells from different stem cell sources for cellular therapy. Even though insulin-secreting cells can be generated from a variety of stem cell types like pluripotent stem cells and embryonic stem cells, the ideal functional cells should be generated from patients' own cells and expanded to considerable levels by non-integrative culture techniques. In terms of the ease of isolation, plasticity, and clinical translation to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 139 publications
0
31
0
Order By: Relevance
“…In MSC-based protocols, two main step IPC differentiation were involved. The initial stage, MSCs were induced into pancreatic progenitor followed by βcell maturation [45]. However, three-stage differentiation protocol was involved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In MSC-based protocols, two main step IPC differentiation were involved. The initial stage, MSCs were induced into pancreatic progenitor followed by βcell maturation [45]. However, three-stage differentiation protocol was involved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to immunomodulatory functions and paracrine signaling, the differentiation potential of WJ-MSCs down several lineages adds a lot to their therapeutic potential, not only for DM, but also for a wide array of other diseases (Can et al, 2017). In fact, several pre-clinical studies reported the differentiation potential of WJ-MSCs into insulin producing cells (IPCs) using various induction protocols, and inducing extrinsic factors (Kassem et al, 2016;Pavathuparambil Abdul Manaph et al, 2019).…”
Section: Differentiation and Cell Replacement Potential Of Wj-mscsmentioning
confidence: 99%
“…But still on the other hand, several elegant studies and review articles attempt to investigate the differentiation potential of MSCs into various lineages other than mesoderm (Urrutia et al, 2019). Insulin producing cells is definitely one of these lineages (Enderami et al, 2018;Päth et al, 2019;Pavathuparambil Abdul Manaph et al, 2019). Accordingly, we recommend that interested scientists should also consider developing novel strategies and enhancing induction protocols to generate IPCs from these WJ-MSCs.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recent studies have further highlighted MSCs’ rich potential as a cell source in revealing these cells’ capacity to differentiate not only into the “classic” MSC cell lineages reported in dozens of studies (e.g., chondrocytes, osteoblasts and adipocytes) [ 9 , 25 , 26 , 27 ] but also into additional cell types, including the following ( Figure 2 )—hepatocytes [ 28 , 29 , 30 ] ( Figure 2 A), cardiomyocytes [ 31 , 32 , 33 , 34 ] ( Figure 2 B), neurons [ 35 , 36 , 37 , 38 ] ( Figure 2 C), epithelium [ 39 , 40 ] ( Figure 2 D), endothelial cells [ 41 , 42 , 43 ] ( Figure 2 E), pancreatic β cells [ 44 , 45 , 46 ] ( Figure 2 F) and epidermis [ 47 , 48 , 49 ] ( Figure 2 G). It remains a challenge to develop methods that elicit MSC differentiation into other cell types such as gut, lung and microglial cells.…”
Section: Mesenchymal Stem Cells As a Cell Sourcementioning
confidence: 99%